Associations of Smoking and Drinking with New Lipid-Related Indices in Women with Hyperglycemia - Ichiro Wakabayashi (Mary Ann Liebert, 2021)
Background: Lipid-related indices are useful for early detection of the risk of cardiovascular disease. The relationships of smoking and alcohol drinking with lipid-related indices in women with diabetes remain to be clarified. Methods: In female participants with hyperglycemia, four lipid-related indices, ratio of low-density lipoprotein cholesterol to high-density lipoprotein cholesterol (LDL-C/HDL-C ratio), atherogenic index of plasma (AIP), lipid accumulation product (LAP), and cardiometabolic index (CMI), were compared in smokers and nonsmokers and in occasional drinkers, regular drinkers, and nondrinkers. Analysis of covariance and logistic regression analysis were used for comparison with adjustment for age, hemoglobin A1c, history of regular exercise, and history of alcohol drinking or smoking. Results: Mean levels of LDL-C/HDL-C ratio, AIP, and CMI were significantly higher in smokers than in nonsmokers, and the odds ratios in smokers versus nonsmokers for high LDL-C/HDL-C ratio, high AIP, and high CMI were significantly higher than the reference level. These differences in mean levels and odds ratios were not found in analysis of LAP. Mean levels of LDL-C/HDL-C ratio, LAP, AIP, and CMI were significantly lower in regular drinkers than in nondrinkers. The odds ratios versus nondrinkers for high LDL-C/HDL-C ratio, high AIP, high LAP, and high CMI in regular drinkers were significantly lower than the reference level. The odds ratios versus nondrinkers for high LDL-C/HDL-C ratio, high LAP, and high CMI in occasional drinkers were also significantly lower than the reference level. Conclusions: In women with hyperglycemia, smoking was positively associated with LDL-C/HDL-C ratio, AIP, and CMI, and habitual alcohol drinking was inversely associated with LDL-C/HDL-C ratio, AIP, LAP, and CMI. Thus, LDL-C/HDL-C ratio, AIP, and CMI are thought to be affected by both smoking and alcohol drinking, which accelerates and suppresses atherosclerotic progression, respectively.